Pewarnaan Titik Ketakteraturan Lokal Inklusif pada Keluarga Graf Unicyclic - Arika Indah Kristiana; Muhammad Gufronil Halim; Robiatul Adawiyah (Universitas Airlangga, 2022)
The graph in this paper is a simple and connected graph with V(G) is vertex set and E(G) is edge set. An inklusif local irregularity vertex coloring is defined should be maping l:V(G) à 1,2,…, k as vertex labeling and wi : V(G) à N is function of inclusive local irregularity vertex coloring, with wi(v) = l(v) + ∑u∈N(v) l(u) in other words, an inclusive local irregularity vertex coloring is to assign a color to the graph with the resulting weight value by adding up the labels of the vertices that are should be neighboring to its own label. The minimum number of colors produced from inclusive local irregularity vertex coloring of graph G is called inclusive chromatic number local irregularity, denoted by Xlisi(G). Should be in this paper, we learn about the inclusive local irregularity vertex coloring and determine the chromatic number on unicyclic graphs.